Transition Metal‐Free One‐Pot Protocol Toward Conjugated Arylbutadiynyl Sulfides. Issue 6 (7th September 2015) - Zhang, Yanqin; Xiao, Jing; Dong, Wanrong; Peng, Zhihong; An, Delie
ABSTRACT: An efficient strategy toward conjugated arylbuta‐1, 3‐diynyl sulfides (Ar–C≡C–C≡C–SR) was herein reported. In the newly developed one‐pot, three‐steps protocol, the synthetically or materially significant arylbuta‐1, 3‐diynyl sulfides were obtained from easily accessible 4‐hydrocarbylthio‐1‐arylbuta‐1, 3‐diones, avoiding usage of expensive terminal aryl acetylenes as substrates or any transition metal complexes as catalysts. The gram‐scale experiment of the efficient methodology with acceptable yield afforded a good alternative of industrial interest.